Predisposition Factors Related to Stunting Preventing Behaviors - Anita, Wan; Islami Zalni, Rummy; Widadari Aldinda, Tharra (STIKes Patria Husada Blitar, 2025)
Stunting is a child growth disorder characterized by a child's lack of height compared to children his age. Morbidity and mortality rates, decreased growth, learning achievement, increased risk of infectious and non-communicable diseases, and decreased productivity are all effects of stunting. This research aimed to find predisposing factors that contribute to stunting preventing behaviors. This research focused on the working area of Sidomulyo Inpatient Health Center. The research design was cross-sectional, with 95 mother subjects. The measurement used a questionnaire. Research results from bivariate analysis using chi square analysis showed that there was a correlation between age (p-value 0.022), occupation (p-value 0.024), education (p-value 0.000), and knowledge (p-value 0.015) with the level of stunting. It is recommended to the community and families who will have children under five that the mother's age, occupation, education and knowledge influence their behavior in preventing stunting. Health workers can provide counseling or education about predisposing factors related to stunting prevention behavior to their patients.